Optimization of a high‐resolution radical scavenging assay coupled on‐line to reversed‐phase liquid chromatography for antioxidant detection in complex natural extracts. Issue 5 (27th January 2015) - De Smet, Seppe; Miserez, Bram; Rambla Alegre, Maria; Talha Yapa, Mehmet; de Villiers, André; Sandra, Pat; Lynen, Frederic
<x xml:space="preserve">Abstract</x> This paper reports the optimization of the on‐line coupling of 2, 2′‐azinobis(3‐ethylbenzothiazoline)‐6‐sulfonic acid based radical scavenging assays with reversed‐phase high‐performance liquid chromatography. The residence time in the reactor was reduced to 6.4 s to ensure minimal peak broadening and loss of separation. Peak capacity losses between compound detection and measurement of the radical scavenging potential were reduced to 10% and lower on coupled column systems. The methodology was successfully applied for the detection of the scavenging activity of molecules encompassing a broad hydrophobicity range. The method shows promise for the assessment of low‐molecular‐weight polyphenols in red wine by coupled‐column high‐resolution high‐performance liquid chromatography with mass spectrometry analysis.